2019
DOI: 10.3389/fphar.2019.01241
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ginkgolic Acid in Attenuating LDL Induced Inflammation Human Peripheral Blood Mononuclear Cells via Altering the NF-κB Signaling Pathway

Abstract: Oxidized low-density lipoprotein (ox-LDL) is considered as the significant maker of inflammatory reaction. ox-LDL was reported to play a crucial role in the pathogenesis of atherosclerosis (AS). In the current study, we scrutinize the suppressive effect of ginkgolic acid against ox-LDL induced an oxidative and inflammatory response in human microvascular endothelial cells (HMEC-1) and human peripheral blood mononuclear cells (nPBMCs) and explore the mechanism of action. HMEC-1 cells are treated with ox-LDL in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 98 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Notably, Ginkgolic acid disrupts the early stage of the Alphavirus replication cycle and inhibits the expression of viral proteins structural E1 and non-structural nsP1, showing antiviral activity against the arboviruses [16] . In addition, it has been suggested that Ginkgolic acids effectively inhibit the release of inflammatory mediators and pro-inflammatory cytokines in ox-LDL-induced HUVECs, HMEC-1, and hPBMCs cells by blocking the activation of the NF-κB pathway [14] , [63] .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Ginkgolic acid disrupts the early stage of the Alphavirus replication cycle and inhibits the expression of viral proteins structural E1 and non-structural nsP1, showing antiviral activity against the arboviruses [16] . In addition, it has been suggested that Ginkgolic acids effectively inhibit the release of inflammatory mediators and pro-inflammatory cytokines in ox-LDL-induced HUVECs, HMEC-1, and hPBMCs cells by blocking the activation of the NF-κB pathway [14] , [63] .…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgolic acid is an alkyl phenolic constituent extracted from the Ginkgo biloba [28]. Previous studies have shown that GA possesses numerous biological activities, including anti-inflammatory, anti-tumor, and anti-bacterial [35] [36]. Here, we demonstrated that GA inhibited necroptosis, inflammatory responses, and endothelial damage in vascular tissues.…”
Section: Discussionmentioning
confidence: 50%
“…GA is described as 13:0, 15:0, 15:1, 17:1, and 17:2 based on the differences of side-chain carbon atoms and double bonds. Current studies have revealed that the biological activities of GA include antitumor, anti-inflammatory, neuroprotective, and antianxiety activities, antimicrobial activities in vitro ( 9 13 ), and broad antiviral activities against herpes simplex virus 1 (HSV-1), HIV, Ebola virus (EBOV), influenza A virus (IAV), Epstein Barr virus (EBV), and Chikungunya, Mayaro, Una, and Zika viruses by blocking the fusion event ( 12 , 14 16 ). In addition, GA (15:1) was identified as a dominant ingredient that contributed to the antimicrobial activity of Ginkgo extracts ( 17 ).…”
Section: Introductionmentioning
confidence: 99%